Pengelolaan Budgeting Sebagai Perencanaan dan Pengendalian Biaya Operasional Perusahaan Jasa CV Bizplus.id - Natanael Andhika Putra; Yuniningsih (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
Budgetary management plays a key role as the foundation for planning and controlling operational costs to support the effectiveness of activities in service companies. This study aims to analyze the implementation of budgeting as a mechanism for planning and controlling operational costs at CV Bizplus.id. The research employed a qualitative, descriptive design. Data were collected through observation, interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model consisting of data reduction, data display, and conclusion drawing. The findings indicate that budgeting at CV Bizplus.id is implemented by developing operational programs that involve each division to identify needs, set priorities, and allocate budgets in line with the company’s financial capacity. Operational cost control is performed by comparing actual expenditures to the established budget and evaluating any variances. The operational budget realization reached 91% of the total budget, indicating that most operational activities were carried out as planned without exceeding budget limits. Therefore, the application of budgeting at CV Bizplus.id effectively supports planning and control of operational costs and provides a basis for management evaluation and decision-making.